2014
DOI: 10.1364/oe.22.011680
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering reveals strong LO-phonon-hole-plasmon coupling in nominally undoped GaAsBi: optical determination of carrier concentration

Abstract: Abstract:We report room-temperature Raman scattering studies of nominally undoped (100) GaAs 1−x Bi x epitaxial layers exhibiting Biinduced (p-type) longitudinal-optical-plasmon-coupled (LOPC) modes for 0.018 ≤ x ≤ 0.048. Redshifts in the GaAs-like optical modes due to alloying are evaluated and are paralleled by strong damping of the LOPC. The relative integrated Raman intensities of LO(Γ) and LOPC A LO /A LOPC are characteristic of heavily doped p-GaAs, with a remarkable near total screening of the LO(Γ) pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 34 publications
6
31
0
Order By: Relevance
“…10 However, as indicated by Steele, these concentrations are higher than those measured by Pettinari et al Hall measurement was performed on these samples. However, the resistance was higher than the system limit and no signal could be captured.…”
Section: -mentioning
confidence: 55%
See 3 more Smart Citations
“…10 However, as indicated by Steele, these concentrations are higher than those measured by Pettinari et al Hall measurement was performed on these samples. However, the resistance was higher than the system limit and no signal could be captured.…”
Section: -mentioning
confidence: 55%
“…A. Steele et al,10 showed that the relative intensity of the Bi-induced longitudinal-opticalplasmon-coupled (LOPC) mode to the GaAs longitudinal-optical (LO) phonon (Γ) is positively related to hole concentration, as shown earlier in numerous earlier studies of doped GaAs.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…As N is increased, ! (near the LO phonon frequency for low N) is driven to higher frequencies as it approaches the avoided crossing (defined by the plasma frequency), forcing significant changes in reflectance [28]. Harima et al demonstrated this effect statically using Raman scattering of SiC epitaxial layers with different ionized dopant levels [13,19], while others have used modified graphene overlaid on SiC to statically tune the permittivity [29,30].…”
Section: Resultsmentioning
confidence: 99%